Development and Hardware-in-the-Loop Simulation of an Air Purifier Automatic Control System - Babunski, Darko; Zaev, Emil; Poposki, Filip; Koleva, Radmila; Rath, Gerhard (IEEE, 2021)
Air pollution is an extraordinarily big problem in developing countries, as well as some metropolitan cities. Infiltration of the outdoor air inside buildings, together with other factors can significantly lower the indoor air quality. Particulate matter (PM) pollution is recognized as one of the biggest problems with regards to indoor air quality. An increasingly popular method for dealing with indoor PM pollution is the use of mobile air purifiers. In this paper, a mathematical model for the indoor PM pollution, and the effect of the purifier is presented. This model is verified using an experimental setup. Then an automatic control system is developed based on the model. Finally, a Hardware-in-the-loop (HIL) simulation of the control system is performed using a Raspberry Pi 4 B and an ST Nucleo-64 board.
Keywords: Hardware-in-the-Loop Simulation, Model-based feedback control, Indoor Air Pollution Modelling, Model Verification